PENGEMBANGAN BUDAYA LITERASI MELALUI LIBRARY TOUR DI UPT PERPUSTAKAAN UNIVERSITAS SEBELAS MARET SURAKARTA - Henny Perwitosari; Hermy Yulianti; Argyo Demartoto (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The purpose of this study was to determine the profile of library tour activities at the UPT Sebelas Maret University Library, Surakarta and to examine the development of community literacy culture through library tour activities. The research method using a quantitative and qualitative descriptive approach. The data collection techniques using survey methods based on data obtained in the field, namely by field observations, interviews, and data documentation. The results of the study show that library tour activities play a high role in the development of literacy culture in the community. The strategy to make library tour activities better in the future is to develop library tour through strengthening of literacy culture based on innovation and creativity. This can be done through improving policy governance at the UPT Sebelas Maret University Library, Surakarta, such as improving facilities and infrastructure, the quality of human resources, and optimizing promotional activities.